1995
DOI: 10.1007/bf02634116
|View full text |Cite
|
Sign up to set email alerts
|

Milk-derived growth factors as serum supplements for the growth of fibroblast and epithelial cells

Abstract: We have investigated the response of several epithelial and fibroblastic cells to a mitogenic extract of bovine milk. Cation exchange chromatography was used to produce a mitogen-rich fraction from an industrial whey source that, although comprising only 0.5% of total whey protein, contained the bulk of the growth factor activity. This fraction was a source of potent growth promoting activity for all mesodermal-derived cells tested, including human skin and embryonic lung fibroblasts, Balb/c 3T3 fibroblasts, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 22 publications
3
51
0
4
Order By: Relevance
“…No conjunto, essas substâncias têm sido chamadas de fatores de crescimento celular, incluindo neste grupo, além da lactoferrina 18 , uma série de polipeptídios, incluindo os fatores de crescimento semelhantes à insulina I e II (IGF-I e IGF-II), fatores ácidos e básicos de estímulo ao crescimento de fibroblastos (aFGF, bFGF), fatores de transformação de tecidos (TGF-β 1 e TGF-β 2 ), além de vários outros não identificados 69 . No conjunto, essas substâncias estimulam a proliferação (mitogênese) de variados tipos de células, podendo substituir, em boa parte, o soro fetal bovino comercializado com esta finalidade.…”
Section: Outros Benefíciosunclassified
See 1 more Smart Citation
“…No conjunto, essas substâncias têm sido chamadas de fatores de crescimento celular, incluindo neste grupo, além da lactoferrina 18 , uma série de polipeptídios, incluindo os fatores de crescimento semelhantes à insulina I e II (IGF-I e IGF-II), fatores ácidos e básicos de estímulo ao crescimento de fibroblastos (aFGF, bFGF), fatores de transformação de tecidos (TGF-β 1 e TGF-β 2 ), além de vários outros não identificados 69 . No conjunto, essas substâncias estimulam a proliferação (mitogênese) de variados tipos de células, podendo substituir, em boa parte, o soro fetal bovino comercializado com esta finalidade.…”
Section: Outros Benefíciosunclassified
“…No conjunto, essas substâncias estimulam a proliferação (mitogênese) de variados tipos de células, podendo substituir, em boa parte, o soro fetal bovino comercializado com esta finalidade. Pesquisadores australianos 69 estabeleceram metodologias em nível piloto, para o isolamento desses fatores do soro de leite, como um concentrado, estudando sua ação não somente como estimulador do crescimento celular, mas também, como agente reparador de feridas crônicas 70 . Um extrato total desses fatores de crescimento estimulou o crescimento de fibroblastos com potência várias vezes maior que o observado para o soro fetal bovino.…”
Section: Outros Benefíciosunclassified
“…Besides having low bacterial content (3,4), physiologic osmolality (230-270 mOsm/kg) and neutral pH (6.5-6.8), it provides the cells with nutrients (3) and growth factors (12,13). Although there has been some controversy (6,8), it has been suggested that milk with a lower fat content might be more appropriate to maintain PDLF viability than milk with a higher fat content (14).…”
Section: Introductionmentioning
confidence: 99%
“…This whey growth factor extract (WGFE) has been shown to be remarkably potent in stimulating the growth in itro of cells of mesodermal origin, including rat L6 myoblasts and Balb\c 3T3 fibroblasts [31]. Several growth factors have been identified in this extract, including fibroblast growth factors 1 and 2 (FGF-1 and FGF-2) [32], IGF-I and IGF-II, PDGF and TGF-β [33].…”
Section: Introductionmentioning
confidence: 99%